Avaliação de métodos de seleção de anti-incrustantes fosfonatados para reservatórios de petróleo - Oliveira, Arthur Reys Carvalho de (2017)
To reduce the damage of scaling during oil extraction, the application of inhibitors is the most widespread technique for such problems. Due to the complex interactions between saline solution and inhibitors, empirical methods are used in their selection. The most used in the oil industry are: the static, standardized of the Standard TM0374-2007 in the National Associatio n of Corrosion Engineers (NACE) , and a dynamic, known as tube block test or TBT (tube blocking test). The NACE does not correlate with actual field performance, while TBT enables the reproducibility of nearer operating conditions. In this study, the two methods are tested for two antifouling based on phosphonic acids, aminotrismethylenephosphonic acid and diethylenetriaminepentamethylenephosphon ic acid (known as tris and penta, respectively), in determining the minimum inhibitor concentration (MIC). We evaluated the advantages and disadvantages of each method and its ability to discriminate the two inhibitors. In order to deepen the understanding of the mechanisms of interaction between inhibitor and brine, adsorption curves were raised for the two inhibitors and we applied a theoretical prediction model of the MIC for the dynamic method. We conclude that the methods studied presented similar resu lts regarding the valu es efficiencies of the antifouling, indicating a better penta performance. Regarding the differences, the NACE method was notable for its ease of execution, but it was limited because it did not consider factors such as variations in pressure and temper ature, indicating a minimum inhibitor concentration between 1 ppm < MIC < 3 ppm. The TBT was distinguished by incorporating variables closer to the reservoir conditions and essential in the CaCO 3 precipitation, but presented the disadvantage of relating de posit formation with the dimensions and the brine composition. In this, a minimum inhibitor concentration was found between 3 ppm < MIC < 5 ppm. These differences are explained in terms of residence times that are much longer in the static method (a few ho urs) than in the dynamic method (a few minutes). The adsorption curves show a large difference in the adsorbed amount of the inhibitors, in which the penta adsorbed ten times more than the tris. This difference is much greater than that found in empirical methods, indicating that adsorption, although important, is not the predominant mechanism in the inhibitor - brine interaction. Finally, the theoretical calculation of MIC was, approximately, 4,6 ppm, in agreement with the TBT test result. The theoretical mo del also predicts WCM of 77 ppm for the most severe condition with high Ca 2+ concentration.